Ecomyopia on the Chesapeake: social and cultural barriers to climate-induced managed retreat - Casagrande, David G.; Lampman, Aaron (Frontiers in Climate, 2025)
Ecomyopia is the tendency to ignore important environmental information that challenges structures of power and place-based identities. Predictions of relative sea-level rise on the Eastern Shore of Maryland include catastrophic land loss over the next 50 years but have not promoted serious discussion about managed retreat. We review literature emerging from Mary Douglas’ theory of the cultural construction of environmental risk and psychological theories of cognitive dissonance and social identity to examine why many residents of the Chesapeake Bay resist relocation in the face of rising sea level. We use this theoretical synthesis to analyze 63 in-depth interviews conducted on the Eastern Shore of the Chesapeake Bay to examine how social institutions and widely shared narratives of heritage and identity frame discussion of sea-level rise. Technological solutions to shoreline erosion dominate the discourse as a means of avoiding cognitive dissonance caused by relocation’s existential threat to place-based identity. As predicted by the Cultural Theory of Risk, group identities shape risk perceptions associated with rising sea level and climate change. Discourse in our case study illustrates how confirmation bias is a social process and why those who challenge the status quo are marginalized as environmental information is transformed into preferred solutions. We generalize from this case study to explain how ecomyopia can preclude managed retreat as a rational strategy in regions threatened by anthropogenic climate change and rising sea levels.